Transformasi Kepemimpinan Adaptif, Visioner, dan Inklusif dalam Meningkatkan Mutu Pendidikan Pada Era Disrupsi Global: The Transformation of Adaptive, Visionary, and Inclusive Leadership in Enhancing Educational Quality in the Era of Global Disruption - Sudiansyah, Sudiansyah; Peterianus, Septian (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
In the context of increasingly complex global changes and technological disruption, educational leadership faces strategic challenges that necessitate a multidimensional approach. This research aims to examine various educational leadership models through a multidisciplinary qualitative approach and a literature review of 45 national and international references. Thematic analysis was employed to identify leadership patterns, values, and strategies relevant to the era of disruption. The findings reveal ten thematic leadership categories consolidated into four main pillars: leadership styles, transformation strategies, educational quality, and responses to disruption. The results indicate that transformational, visionary, adaptive, and inclusive leadership styles are instrumental in enhancing the effectiveness of educational institutions. Furthermore, digital, instructional, and spirituality-based leadership enrich the ethical and innovative dimensions of institutional governance. The conclusion affirms the importance of synthesizing classical and contemporary approaches, as well as the need to develop contextual leadership models that are integrative and grounded in local wisdom. This study contributes to the development of leadership theory and practice that is reflective, collaborative, and responsive to the educational challenges of the 21st century.